Mathematics for Elementary Teachers: A Conceptual Approach - Bennett Albert B (McGraw -Hill, 2006)
Emphasizing conceptual understanding through the use of models and visuals, this new text helps students connect ideas and concepts while providing them with useful methods for teaching math to elementary school children. Mathematics for Elementary Teachers: A Conceptual Approach also addresses the latest NCTM standards by increasing the use of technology, adding "Math Activities" sections, and developing new methodology materials called "Ideas for the Classroom." These math activities serve as a set of inductive activities for prospective elementary and secondary teachers that use physical models, manipulatives, and visual images to develop concepts and encourage higher level thinking. --This text refers to an out of print or unavailable edition of this title.